Predator identity more than predator richness structures aquatic microbial assemblages in Sarracenia purpurea leaves. Issue 3 (25th January 2018) - Canter, Erin J.; Cuellar‐Gempeler, Catalina; Pastore, Abigail I.; Miller, Thomas E.; Mason, Olivia U.
Abstract: The importance of predators in influencing community structure is a well‐studied area of ecology. However, few studies test ecological hypotheses of predation in multi‐predator microbial communities. The phytotelmic community found within the water‐filled leaves of the pitcher plant, Sarracenia purpurea, exhibits a simple trophic structure that includes multiple protozoan predators and microbial prey. Using this system, we sought to determine whether different predators target distinct microorganisms, how interactions among protozoans affect resource (microorganism) use, and how predator diversity affects prey community diversity. In particular, we endeavored to determine if protozoa followed known ecological patterns such as keystone predation or generalist predation. For these experiments, replicate inquiline microbial communities were maintained for seven days with five protozoan species. Microbial community structure was determined by 16S rRNA gene amplicon sequencing (iTag) and analysis. Compared to the control (no protozoa), two ciliates followed patterns of keystone predation by increasing microbial evenness. In pairwise competition treatments with a generalist flagellate, prey communities resembled the microbial communities of the respective keystone predator in monoculture. The relative abundance of the most common bacterial Operational Taxonomic Unit (OTU) in our system decreased compared to the control in the presence of these ciliates. This OTU was 98% similar to a known chitin degrader and nitrate reducer, important functions for the microbial community and the plant host. Collectively, the data demonstrated that predator identity had a greater effect on prey diversity and composition than overall predator diversity.